PREVALENCE OF MARKERS OF VIRAL HEPATITIS B AND D FROM HEALTHY POPULATION IN REPUBLIC TYVA - T. V. Kozhanova; L. Yu. Ilchenko; V. V. Klushkina; M. A. Lopatukhina; E. P. Amon; A. A. Saryglar; O. V. Isaeva; K. K. Kyuregyan; M. I. Michailov (Детские инфекции (Москва), 2015)
Aim: to estimate prevalence of markers, genetic diversity, risk factors of HBV and HDV infections in all age groups among healthy population in Republic Tyva. Serum samples obtained from healthy population in Republic Tyva (N = 1086) were tested (aged from birth to older 60 years). The markers of HBV and HDV infections were determined by enzyme immunoassay and PCR. HBsAg was detected in 7,7% (84/1086), anti-HBc — in 47,8% (519/1086) and HBeAg — in 0,3% (3/1086) cases. Prevalence of HBsAg in children under 9 years was 1,3%, no positive results of anti-HDV were determined among children aged up to 9 year. Prevalence of anti-HDV among HBsAg-positive individuals of healthy population was 32,1% (27/84). HBV DNA was detected in 2,9% (31/1086) cases; HDV RNA — in 32,1% (14/84) HBsAg-positive individuals. The obtained data showed high prevalence of HBV ang HDV infections among healthy population of Republic Tyva. Thus, it is necessary to extend screening program in this region to improve viral hepatitis surveillance and diagnostics. The sharp decline in the prevalence of these infections in children up to 9 years in the surveyed endemic region is an evidence of effective protection against HBV and HDV with vaccination against hepatitis B.